The effect of graphene nanoplatelets on technical properties of micro- and nano-sized TiO2matrix: a comparative research study on electrical and optical characteristics - Guler, Omer; Ayhan, Hakan; Basgoz, Oykum; Yavuz, Cagdas; Albayrak, Muhammet Gokhan; Evin, Ertan; Yahia, Ibrahim S. (Springer, 2020)
In this study, titanium dioxide (TiO2)-based graphene nanoplatelets (GNPs)-reinforced composite materials were produced and the electrical and optical properties of the composite materials were investigated. Graphene, which was used as a reinforcing material, was produced by using liquid-phase exfoliation method. While the TiO(2)used as matrix material was commercially available for the first group of samples, it was produced by using the sol-gel method for the second group of the samples. Different rates of graphene were added to the TiO(2)powders which were commercially available and produced by using sol-gel method. GNPs used as a reinforcing material were subjected to TEM analysis. The resulting composite materials were structurally examined in SEM and XRD. Then, the changes in electrical conductivity of these composites under the impact of temperature were measured. UV-Vis spectrometers of the samples were taken and their optical properties were determined. When temperature-based electrical examination of the produced composite materials was performed, an increase was observed on the electrical conductivity values in both groups of samples as a result of addition of the reinforcing element. In addition, TiO2-containing composites produced by using sol-gel method had lower electrical conductivity comparing with commercially purchased TiO2-containing composites especially at high temperatures. In the optical measurements, it was observed that there was an increase in the optical bandgap energy range values with GNPs reinforcement but a decrease in the reflectance values.
Keywords: Optoelectronic Properties; Oxide Nanocomposites; Tio2; Tio2/Graphene; Temperature; Sheets; Films